PENGARUH ANTARA PENDIDIKAN AGAMA ISLAM DI SEKOLAH DENGAN PENDIDIKAN AGAMA DALAM KELUARGA - Muhammad Iqbal (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2019)
Religious education in the family is a religious instruction provided by the family, especially those under the parents’ guidance which are focused on practicing the religious teachings onto the children. Education in the family reflects the success of children in school or in society. A harmonious family offers more values in a children's life when achieving theier goals. The purpose of this research was to find out how the influence of Islamic religious education in schools with family religious education applied by parents as their responsibility to their children in Arongan Lambalek, West Aceh. This research was a descriptive study that used observation, interviews, documentation and focus group discussion to collect research data. Different data collection techniques or triangulations were used to analyze the research. The result of study showed that there was an influence between Islamic religious education in schools with religious instruction in the family, which assumed responsibility for Islamic religious education for children. It was found that the teacher acts only as a substitute for parents who provide Islamic religious education in schools in the form of subject matter. During the practice and application, the responsibility lies with the parents, who are religious educators in the family. Islamic religious education for children must be integrated between religious education in the family and at school.